Submorphological approach to the [a] morpheme in Spanish and Italian : report and questions (Signifiances (Signifying), 2023)
We briefly present research that go in the direction of phonemes, considered as "articulatory gestures", a concept used in particular by the articulatory phonology which speaks of "primitive phonological" as abstract unity, without establishing a necessary link between the physical reality of a sound and its phonological representation. The Spanish approach explores cognematic theory through the study of the (sub) morpheme in [a] Spanish. Following an analysis for Italian on the motivation of the sign through this vowel formant.